Comparative Evaluation of Pain During Local Anaesthetic Administration with Conventional and Custom Modified Syringe in Pediatric Dental Patient: A Clinical Trail (Academia Journal of Medicine, 2025)
Aim: This clinical trial aimed to evaluate and compare the pain experienced during local  anaesthetic administration using a conventional syringe versus a custom modified syringe  designed with attractive emojis. The hypothesis was that the custom syringe would decrease  anxiety and perceived pain. Materials and Methods: Thirty pediatric dental patients of age 6-8 years were randomly  assigned to receive local anaesthesia with either a conventional disposable syringe or a custom  modified syringe, decorated with vibrant, engaging emoji stickers. Pain levels were assessed  immediately after the injection using the Wong-Baker FACES Pain Rating Scale, allowing  patients to express their pain intensity through visual representation. Data were collected and  analyzed to compare pain scores between the two groups. Results: The findings indicated that patients using the custom modified syringe reported  significantly lower pain scores than those using the conventional syringe. The visual appeal  of the custom syringe appeared to reduce anxiety, contributing to a more positive experience  during the procedure. Conclusion: The incorporation of attractive emojis on syringes may serve as an effective  strategy to reduce pain and anxiety associated with local anaesthetic administration. These  findings suggest potential benefits for enhancing patient comfort and compliance in clinical  settings. Further research is warranted to explore the long-term impact of such modifications  on patient experiences in various medical procedures.
Keywords: Pain; Local Anesthesia; Wong-Baker FACES Pain Rating Scale